Analysis Error Student In Learning Geometry As Base Understanding Non-Euclidean Geometry : An Overview Literature Based on Newman's Error Analysis - Dosta Ernauli Siregar; Lasvina Br. Purba; Jesica Dhea Chyntia; KMS Muhammad Amin Fauzi (PT. Padang Tekno Corp, 2025)
This study aims to identify the dominant error patterns of students in geometry learning based on Newman's Error Analysis (NEA) and to examine their implications for readiness to understand Non-Euclidean Geometry. The method employed is a Systematic Literature Review (SLR) of 10 empirical articles published between 2019 and 2026. Data were extracted based on the five stages of NEA — reading, comprehension, transformation, process skill, and encoding — and subsequently analyzed through narrative synthesis, percentage comparison, and descriptive effect size. The results indicate that comprehension errors and encoding errors are the most dominant categories, with the highest percentages of 56.92% and 50%, respectively, followed by transformation errors, which consistently fall within a moderate effect range (20–40%), while reading errors and process skill errors are classified as low. The primary causes of errors include weak understanding of geometric concepts, inability in spatial visualization, limited mathematical language, and lack of procedural precision. The findings contribute as a diagnostic foundation for designing more effective geometry learning, while simultaneously serving as a conceptual bridge toward higher-level geometry